Hubungan antara Stres Kerja, dan Motivasi Kerja terhadap Produktivitas Karyawan di Indonesia - Fitry R Lubis, Adelina; Susilawati, Susilawati (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2024)
Work stress is a condition that causes physical and mental imbalance which can affect employees' emotions, thought processes, and working conditions. Work motivation can be defined as the desire and drive that a person has to carry out their work actively and purposefully to achieve certain goals. This research uses a literature review methodology that focuses on variables or topics studied from previous research. The act of reviewing literature involves collecting data from libraries and documentation. Research articles and literature reviews obtained data related to the relationship between work stress and work motivation on employee productivity in Indonesia. By using predetermined inclusion criteria, namely complete scientific publications published in the last five years, the procedure for collecting articles is carried out by searching literature sources. Review literature sources can be found using the following keywords in Google Scholar: The Influence of Job Stress and Work Motivation on Employee Work Productivity at PT Reinsurance National Indonesia.